Silvo-pastoral systems and public policies in Latin America: A comparative analysis - Moreno, Leonardo; Díaz, Manuel F.; Burkart, Stefan (International Center for Tropical Agriculture, 2021)
Latin America and the Caribbean play an essential role in the global cattle sector since they contribute more than 25% of the global beef and 10% of the global milk production. The sector generates both internal and external benefits as it guarantees the food security of the countries and energizes their economies. Cattle production in the region not only goes back a long way but also appears to be anticipating a promising future. Considering global population growth, it is projected that by 2050 meat consumption will increase by 100%, a scenario that would favor Latin American cattle producers because of their geographical location and available human and natural resources.